The miracle of life [videorecording] - Nilsson, Lennart (NOVA series, 1986)
A documentary which shows the actual conception and development of a baby. Looks inside the male and female reproductive organs to show the formation of sperm and the passage of a fertilized egg through the fallopian tube. Uses a microscope to observe DNA, chromosomes, and other minute body details building up to the moment of birth.